EU Financial Market Access After Brexit - Karel Lannoo (Intereconomics, 2016)
Brexit means Brexit, or out means out — and that includes the UK's exit from the single financial market. With financial services accounting for about eight per cent of the country's GDP, it is understandable why the UK attaches immense importance to retaining access to the EU's single market. But putting a mutually acceptable regime in place will take years of negotiations, and the final agreement will clearly allow much less access than UK-licensed firms enjoy today.
Keywords: 330